MENGUAK KEBENARAN ILMU PENGETAHUAN DAN APLIKASINYA DALAM KEGIATAN PERKULIAHAN - Wahana, Paulus (Jurnal Filsafat "WISDOM", 2008)
AbstractIn discussing about lecturing (teaching and learning) at thehigher education, we are usually too much concerned with theapproaches, methods, media of lecturing, but do seldom or even never pay attention to the objectives of lecturing. We are too much occupied with changing from one method of lecturing to another, for example, from active learning method, contextual method, constructivistic method, student-based curriculum, school-based curriculum, competence-based curriculum, up to curriculum of lesson unit level.Such a complicated thinking is futile unless people are reallyconcerned with directions and objectives of the lecturing activities. In term of lecturing as a way of thinking, the planned activities, we need previously to find out the direction and the goals of the activities, and then we may draw our attention to the methods in order to reach the targeted goals. The targeted goals of lecturing are making students think clearly and distinctly, making students can find the truth of scientific knowledge, making students become problem finders and problem solvers.As academic activities, the lecturing processes should be held scientifically. In addition to obtaining clear scientific stuffs, the lecturing activities should support the students to find the truthof science.After comprehending all types of truth, we may start to find out the description of scientific truth, as the targeted goal to pursue in the scientific activities. Furthermore, we may try to reveal and to find the truth of scientific knowledge in the lecturing activities.Through finding out the description of the truth during the lecturing activities, we expect to have appropriate orientation and steps of implementing the lecturing activities in order to reach the targeted goals of lecturing. By reaching the goals of lecturing, the students are expected to find some benefits from the lecturing activities. Then the activities will not be considered as burden for the students, but rather as the activities resulting in mental richness, generating enlightenment, and increasing students’ abilities.Keywords: lecturing activities, lecturing objectives, targeted goals, enlightenment, scientific truth, mental richness.